Application of Novel Thermal AFM Scanning Probe Techniques in the Adhesion Studies of E. coli Cells - Y. Dragnevska, Zdravka; Reading, Mike; Q.M. Craig, Duncan (Micro and Nanosystems, 2012)
Atomic Force Microscopy was successfully employed to measure for the first time the interactive forces between different types of heated probes and E. coli bacterial cells. The results indicate that within a narrow temperature range there is a step decrease in the pull-off force and thus the adhesion between the tip and the sample. This adhesion measurement is a method of probing the interactions between the tip and the cell and the step change can be associated with structural changes taking place on the surface of the bacterium. This methodology gave reproducible results although some aspects of the force distance curves are not yet understood. This study indicates that the use of heated probes can be used to measure thermal transitions in biological systems and this approach could be extended to study how temperature affects specific cell surface interactions using functionalised tips.
Keywords: PE